The Role of Artificial Intelligence in Cardiovascular Imaging: State of the Art Review - Seetharam, Karthik; Brito, Daniel; Farjo, Peter D.; Sengupta, Partho P. (Frontiers in Cardiovascular Medicine, 2020)
In this current digital landscape, artificial intelligence (AI) has established itself as a powerful tool in the commercial industry and is an evolving technology in healthcare. Cutting-edge imaging modalities outputting multi-dimensional data are becoming increasingly complex. In this era of data explosion, the field of cardiovascular imaging is undergoing a paradigm shift toward machine learning (ML) driven platforms. These diverse algorithms can seamlessly analyze information and automate a range of tasks. In this review article, we explore the role of ML in the field of cardiovascular imaging.